Type-3 Fuzzy Based Secondary Voltage and Frequency Restoration Control of Inverter Based Microgrids with Droop Control - Düzdağ, Muhammed Serhat; Kılıç, Heybet; Haydaroglu, Cem (Fırat University, 2024)
The environmental impacts and sustainability problems of traditional energy sources force the energy sector to make some changes. In this context, renewable energy sources, especially energy obtained from natural sources such as solar, wind and hydroelectricity, are of increasing importance. These resources have the potential to overcome the disadvantages of traditional energy sources by providing environmentally friendly and sustainable energy production. However, in order to use renewable energy resources effectively, it is necessary to focus on the changing dynamics in the energy sector. These dynamics include issues such as the environmentally unfriendly nature of traditional energy sources, energy security and environmental order. At this point, microgrids come into play and offer a structure that integrates energy production, storage and consumption. Although microgrids provide advantages such as increasing local energy production and increasing energy efficiency, they also bring some disadvantages. In this context, the article discusses in detail voltage and frequency control, a fundamental component of microgrids, emphasizing the critical importance of this issue for the stable operation of microgrids. Type-3 fuzzy control (T3-FLC) method stands out for improving voltage and frequency control in microgrids. T3-FLC provides parallel operation by providing an effective control structure, especially in microgrids with highly distributed generation. This article stands out as an important resource to deeply understand the role of microgrids in the energy sector and contribute to sustainable energy production.

Geleneksel enerji kaynaklarının çevresel etkileri ve sürdürülebilirlik sorunları, enerji sektörünü bir takım değişimlere zorlamaktadır. Bu bağlamda, yenilenebilir enerji kaynakları, özellikle güneş, rüzgar ve hidroelektrik gibi doğal kaynaklardan elde edilen enerji, giderek artan bir öneme sahiptir. Bu kaynaklar, çevre dostu ve sürdürülebilir enerji üretimi sağlayarak, geleneksel enerji kaynaklarının dezavantajlarını aşma potansiyeli taşımaktadır. Ancak, yenilenebilir enerji kaynaklarının etkin bir şekilde kullanılabilmesi için, enerji sektöründeki değişken dinamiklere odaklanmak gerekmektedir. Bu dinamikler arasında, geleneksel enerji kaynaklarının çevre dostu olmayan yapısı, enerji güvenliği ve çevresel düzen gibi konular bulunmaktadır. Bu noktada, mikro şebekeler devreye girmekte ve enerji üretimi, depolama ve tüketimi entegre eden bir yapı sunmaktadır. Mikro şebekeler, yerel enerji üretiminin artırılması ve enerji verimliliğinin arttırılması gibi avantajlar sağlamakla birlikte, beraberinde bir takım dezavantajları da getirmektedir. Bu bağlamda, makale, mikro şebekelerin temel bir bileşeni olan gerilim ve frekans kontrolünü detaylı bir şekilde ele alarak, bu konunun mikro şebekelerin istikrarlı çalışması için kritik önemini vurgulamaktadır. Mikro şebekelerde gerilim ve frekans kontrolünün iyileştirilmesi için tip-3 bulanık kontrol (T3-BMK) yöntemi öne çıkmaktadır. T3-BMK, özellikle çok dağıtık üretim sahip mikro şebekelerde etkili bir kontrol yapısı sunarak paralel çalışma olanağı tanımaktadır. Bu makale, mikro şebekelerin enerji sektöründeki rolünü derinlemesine anlamak ve sürdürülebilir enerji üretimine katkı sağlamak adına önemli bir kaynak olarak öne çıkmaktadır.
Tip-3 Bulanık Mantık ile Düşüş Kontrollü İnverter Tabanlı Mikro Şebekelerin İkincil Gerilim ve Frekans Restorasyon Kontrolü
Keywords: Power Plants; Elektrik Tesisleri